Education for Sustainable Development (ESD) Competency in Physics Learning Assessment: Pre-service Teachers' Thinking Skills Based on Ethno-Socio-Scientific Content - Novita, Nanda; Andriani, Riza; Muliani, Muliani; Makfirah , Husnul; Nur'azizah, Nur'azizah (Jurnal Pendidikan IPA Indonesia, 2025)
This research examines the ESD competency levels—specifically systems thinking, anticipatory thinking, and critical thinking—among pre-service physics teachers within ethno-socio-scientific content, aiming to equip future educators with the skills, knowledge, and attitudes needed to promote sustainability and address global environmental and social challenges. A quantitative approach was employed, with a sample of 83 pre-service physics teacher students from a Physics Education program at a university in Aceh, Indonesia. This research instrument consists of eight multiple-choice questions for each competency. Validity and reliability analyses, using the Rasch model, confirmed the instrument's robustness, yielding high-reliability scores (person reliability = 0.82, item reliability = 0.84, Cronbach's alpha = 0.85). The results reveal variations in competency levels: anticipatory thinking is the strongest, critical thinking is the least developed, and systems thinking is moderate. Correlation analysis indicates positive and moderate relationships among the competencies, highlighting the importance of integrated ESD competency development. The success of Education for Sustainable Development (ESD) requires a holistic approach that fosters the development of all relevant competencies. Prioritizing critical thinking is essential, as it is a foundation for enhancing other competencies. Educational systems should focus on cultivating systems thinking and anticipatory thinking, as these are interconnected and mutually reinforcing in the transformation toward sustainability. Additionally, the findings suggest that the comprehensive integration of ESD into the physics education curriculum can enhance pre-service teachers' capacity to engage effectively with sustainability issues. By incorporating ethno-socio-scientific contexts, this approach deepens the ethnic, social, and contextual relevance of physics concepts, thus preparing future educators to address sustainability challenges.